Determining the analytical specificity of PCR-based assays for the diagnosis of IA: What is Aspergillus?. (7th October 2016) - Morton, C. Oliver; White, P. Lewis; Barnes, Rosemary A.; Klingspor, Lena; Cuenca-Estrella, Manuel; Lagrou, Katrien; Bretagne, Stéphane; Melchers, Willem; Mengoli, Carlo; Caliendo, Angela M.; Cogliati, Massimo; Debets-Ossenkopp, Yvette; et al.
Abstract: A wide array of PCR tests has been developed to aid the diagnosis of invasive aspergillosis (IA), providing technical diversity but limiting standardisation and acceptance. Methodological recommendations for testing blood samples using PCR exist, based on achieving optimal assay sensitivity to help exclude IA. Conversely, when testing more invasive samples (BAL, biopsy, CSF) emphasis is placed on confirming disease, so analytical specificity is paramount. This multicenter study examined the analytical specificity of PCR methods for detecting IA by blind testing a panel of DNA extracted from a various fungal species to explore the range of Aspergillus species that could be detected, but also potential cross reactivity with other fungal species. Positivity rates were calculated and regression analysis was performed to determine any associations between technical specifications and performance. The accuracy of Aspergillus genus specific assays was 71.8%, significantly greater ( P < .0001) than assays specific for individual Aspergillus species (47.2%). For genus specific assays the most often missed species were A. lentulus (25.0%), A. versicolor (24.1%), A. terreus (16.1%), A. flavus (15.2%), A. niger (13.4%), and A. fumigatus (6.2%). There was a significant positive association between accuracy and using an Aspergillus genus PCR assay targeting the rRNA genes ( P = .0011). Conversely, there was a significant association between rRNA PCR targets and false positivity ( P = .0032). To conclude current Aspergillus PCR assays are better suited for detecting A. fumigatus, with inferior detection of most other Aspergillus species. The use of an Aspergillus genus specific PCR assay targeting the rRNA genes is preferential.